Comparison of handheld rebound tonometry with Goldmann applanation tonometry in children with glaucoma: a cohort study. Issue 4 (2nd April 2013) - Dahlmann-Noor, Annegret Hella; Puertas, Renata; Tabasa-Lim, Shenille; El-Karmouty, Ahmed; Kadhim, Mustafa; Wride, Nicholas Kloster; Lewis, Amanda; Grosvenor, Dawn; Rai, Poornima; Papadopoulos, Maria; Brookes, John; Bunce, Catey; et al.
Abstract : Objective: To test agreement of two methods to measure intraocular pressure (IOP): rebound tonometry (RBT) and gold standard Goldmann applanation tonometry (GAT) in children with glaucoma. Design: Observational prospective cohort study. Setting: Tertiary paediatric glaucoma clinic at a single centre. Participants: 102 individuals attending a paediatric glaucoma clinic, mean (SD) age 11.85 (3.17), of whom 53 were male. Primary and secondary outcome measures: Intraocular pressure, central corneal thickness, child preference for measurement method. Results: Limits of agreement for intraobserver and interobserver were, respectively, (−2.71, 2.98) mm Hg and (−5.75, 5.97) mm Hg. RBT frequently gave higher readings than GAT and the magnitude of disagreement depend on the level of IOP being assessed. Differences of 10 mm Hg were not uncommon. RBT was the preferred method for 70% of children. Conclusions: There is poor agreement between RBT and GAT in children with glaucoma. RBT frequently and significantly overestimates IOP. However, 'normal' RBT readings are likely to be accurate and may spare children an examination under anaesthesia (EUA). High RBT readings should prompt the practitioner to use another standard method of IOP measurement if possible, or consider the RBT measurement in the context of clinical findings before referring the child to a specialist clinic or considering EUA.